High-Intensity Exercise Improves Fatigue, Sleep, and Mood in Patients With Axial Spondyloarthritis: Secondary Analysis of a Randomized Controlled Trial. Issue 8 (4th May 2020) - Sveaas, Silje Halvorsen; Dagfinrud, Hanne; Berg, Inger Jorid; Provan, Sella Arrestad; Johansen, Melissa Woll; Pedersen, Elisabeth; Bilberg, Annelie
Abstract: Objective: Although exercise is recommended in the treatment of axial spondyloarthritis (axSpa), the focus has been on flexibility, and the effect of high-intensity exercises is unknown. The purpose of this study was to investigate the effect of high-intensity exercises on fatigue, sleep, and mood in patients with axSpA. Methods: In this secondary analysis of a randomized controlled trial, participants were recruited from outpatient clinics at 4 hospitals in Scandinavia. A total of 100 patients with axSpA were randomized to either an exercise group (n = 50) or a control group (n = 50). High-intensity exercise was provided 3 times per week for 3 months and supervised by a physical therapist. The controls received no intervention. Measurements were self-reported at baseline, 3 months, and 12 months: fatigue, using the Fatigue Severity Scale (range = 0–7, 7 = worst, ≥5 = severe); vitality, using the RAND 36-item short-form health survey (SF-36, range = 0–100, 100 = best); sleep, using the Pittsburgh Sleep Quality Index (range = 0–21, 21 = worst, >5 = poor quality); mood, using the General Health Questionnaire 12 (range = 0–36, 36 = worst); and general health, using the EUROQoL (range = 0–100, 100 = best). Results: A total of 38 participants (76%) in the exercise group followed ≥80% of the exercise protocol. At 3 months, there was a significant beneficial effect on fatigue (mean group differences = −0.4, 95% CI = −0.7 to −0.1), vitality (5.0, 95% CI = 1.1 to 10.5), mood (−2, 95% CI = −3.7 to −0.04), and general health (9.0, 95% CI = 3.3 to 14.7) but no effect on sleep (−1.1, 95% CI = −2.1 to 0.2). Compared with the control group, the exercise group had a reduced rate of severe fatigue and poor sleep. No differences were seen between the groups at 12 months. Conclusions: A 3-month exercise program had a beneficial effect on fatigue, sleep, mood, and general health in patients with axSpA at the end of the intervention; however, no long-term effects were seen. Impact: High-intensity cardiorespiratory and strength exercises should be considered as important in exercise programs for patients with axSpA.